2014
DOI: 10.1016/s0140-6736(14)60421-9
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib in radioactive iodine-refractory, locally advanced or metastatic differentiated thyroid cancer: a randomised, double-blind, phase 3 trial

Abstract: Background Patients with radioactive iodine (131I, RAI)-refractory locally advanced or metastatic differentiated thyroid cancer (DTC) have a poor prognosis due to the lack of effective treatment options. Methods This multicentre, randomized (1:1), double-blind, placebo-controlled, phase 3 study (DECISION; NCT00984282) investigated sorafenib (400 mg orally twice-daily) in patients with RAI-refractory locally advanced or metastatic DTC progressing within the past 14 months. The primary endpoint was progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,175
6
56

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,371 publications
(1,311 citation statements)
references
References 30 publications
32
1,175
6
56
Order By: Relevance
“…Lenvatinib is a new treatment option approved for RAI-refractory metastatic or recurrent thyroid carcinoma patients, which achieved outstanding results in comparison with other previous TKIs such as sorafenib [2], vandetanib, and pazopanib. It is an oral multikinase inhibitor of vascular endothelial growth factor (VEGF) receptor (VEGFR)1-3, fibroblast growth factor receptor (FGFR)1-4, platelet-derived growth factor receptor alpha (PDGFR-α), ret proto-oncogene (RET), and KIT proto-oncogene [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Lenvatinib is a new treatment option approved for RAI-refractory metastatic or recurrent thyroid carcinoma patients, which achieved outstanding results in comparison with other previous TKIs such as sorafenib [2], vandetanib, and pazopanib. It is an oral multikinase inhibitor of vascular endothelial growth factor (VEGF) receptor (VEGFR)1-3, fibroblast growth factor receptor (FGFR)1-4, platelet-derived growth factor receptor alpha (PDGFR-α), ret proto-oncogene (RET), and KIT proto-oncogene [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…In none of the patients who presented this AE it was grade 3 (between 50,000 and 25,001 x 10 3 /mm 3 ) or grade 4 (< 25,000 x 10 3 /mm 3 ). Thrombocytopenia was not an AE which led to a dose decreasing or dose interruption in any patient of the DECI-SION trial (10). Nevertheless, in this patient, it seems that this AE was dose dependent because the patient resumed her platelet count to normal after dose reduction to 400 mg/day.…”
Section: Sorafenib Is a Multiple Tyrosine Kinase Inhibitor (Tki) Tarmentioning
confidence: 70%
“…In vitro, it has shown to inhibit multiple kinases thought to be involved in both cell proliferation and angiogenesis. Sorafenib was recently approved in US, Europe and some other countries for the treatment of RAIrefractory and progressive advanced thyroid cancer after the presentation of the DECISION trial which showed that progression-free survival was significantly improved with sorafenib (n = 207) compared with placebo (n = 210) (HR 0.587; 95% CI 0.454-0.758; p < 0.0001; median 10.8 versus 5.8 months, respectively) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Таргетная терапия [1, [229][230][231][232][233][234][235][236][237] Рекомендация 47. Системная таргет-ная терапия препаратами, зарегистрирован-ными в РФ по данным медицинским показа-ниям (сорафениб и ленватиниб), показана при неэффективности РЙТ и доказанном про-грессировании опухоли в течение 3-12 мес согласно критериям RECIST 1.1 в случаях:…”
Section: определение тиреоглобулина и антител к тиреоглобулинуunclassified